2016
DOI: 10.1007/s12041-016-0682-6
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of common MEFV mutations and carrier frequencies in a large cohort of Iranian populations

Abstract: Familial Mediterranean fever (FMF) is a hereditary autoinflammatory disorder caused by mutations in the MEFV gene. The disease is especially common among Armenian, Turkish, Jewish and Middle East Arab populations. To identify the frequency and the spectrum of common MEFV mutations in different Iranian populations, we investigated a cohort of 208 unselected asymptomatic individuals and 743 FMF patients. Nine hundred and fifty-one samples were analysed for the presence of 12 MEFV mutations by PCR and reverse-hyb… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

4
14
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 22 publications
(19 citation statements)
references
References 46 publications
4
14
1
Order By: Relevance
“…A 2.36% prevalence for variants in the MEFV gene was found in our population. Published data about the prevalence of these familiar Mediterranean fever causing variants in Mexican population is lacking, although our study's finding is comparable with those reported in Middle Eastern populations …”
Section: Discussionsupporting
confidence: 87%
“…A 2.36% prevalence for variants in the MEFV gene was found in our population. Published data about the prevalence of these familiar Mediterranean fever causing variants in Mexican population is lacking, although our study's finding is comparable with those reported in Middle Eastern populations …”
Section: Discussionsupporting
confidence: 87%
“…The prevalence of M694I and of the rare form of M680I (M680I G > A) were also relatively high in Italians (10% and 8% respectively). These studies and others [16,17] show that the most prevalent mutations (R761H and K695R) in our study (in Apulia and Basilicata) are actually very rare in the neighbouring countries and islands as well as in relatively far states such as Iran. When we looked for possible sources for the R761H and the K695R mutations (found among our patients), we found that among Turkish Aegean patients with FMF allelic frequencies for the most common mutations were 47Á60% (M694V), 16Á75% (E148Q), 12Á95% (V726A) and 11Á94% (M680I G/C).…”
Section: Discussionsupporting
confidence: 68%
“…The missense mutations R761H (3Á73%) and A744S (2Á24%) were identified as the rarest [15]. These studies and others [16,17] show that the most prevalent mutations (R761H and K695R) in our study (in Apulia and Basilicata) are actually very rare in the neighbouring countries and islands as well as in relatively far states such as Iran. This observation suggests that the origin of the FMF population in Altamura and Matera is probably from small closed families who carried these rare mutations and emigrated together from neighbouring countries or islands (Turkey, Cyprus etc) and settled in these two towns.…”
Section: Discussionsupporting
confidence: 66%
“…However, V726A homozygotes and compound heterozygotes for the V726A/E148Q variants are associated with severe disease, and patients can develop renal amyloidosis. Hence, the authors proposed that patients carrying this complex allele should have been given colchicine prophylaxis [ 9 , 34 ]. In the present study, V726A is the third most common mutation with a frequency of 9.3%.…”
Section: Discussionmentioning
confidence: 99%